Survival Rate and Growth Rate of Transplant Acropora sp and Porites sp Corals in Kecinan, North Lombok - Sigit Hariyanto; Ibadur Rahman; Mahardika Rizqi Himawan (Jurnal Biologi Tropis, 2023)
Coral reef ecosystem is an ecosystem that plays a vital role as spawning floor, feeding floor and nursery ground for marine biota. This study aims to determine the survival and in growth rate of Acropora sp and Porites sp sp corals transplanted using frame media. This research was done in Kecinan Coastal Waters, Malaka Village, Pamenang District, North Lombok Regency. West Nusa Tenggara. The method used in this study an experimental method with 2 month observation, which repeated in every 2 weeks. Coral growth rate is observed twice, at the beginning of coral planting and at the end of the observation. The frame media used were 4 units a size of 1 x 1 m2, which placed 30 coral fragments each. So the total number of coral fragments observed was 120 in the media frame at the same depth. Acropora sp corals that were able to survive until the end of the study reached 96.67% while Porites sp sp corals reached 86.67%. The growth rate of Acropora sp was obtained at a value of 0.51 cm/month, while for Porites sp sp was 0.37 cm/month. The two transplanted corals had different growth forms so that they had different growth rate values. Acropora sp coral had a branching growth form with a hollow and porous limestone structure while Porites sp sp had a massive growth form with a denser and harder limestone skeletal structure.